Clinical, radiographic, and genetic characteristics of hypohidrotic ectodermal dysplasia: A cross‐sectional study. Issue 5 (7th September 2018) - Ngoc, Vo Truong N.; Duong, Nguyen Thuy; Chu, Dinh‐Toi; Hang, Luong M.; Viet, Do H.; Duc, Nguyen M.; Anh, Le Q.; Son, Tong M.; Van Can, Do; Nga, Vu T.
Abstract :